CHALLENGES IN SMALL KNEE ARTHROSCOPY: A QUALITATIVE AND QUANTITATIVE PEDIATRIC CADAVERIC EXPERIENCE. Issue 4 (28th April 2020) - Ellis, Henry; Edmonds, Eric; Yen, Yi-Meng; Wilson, Philip; Tran, Emily; Cannamela, Peter; Shea, Kevin
Background: Arthroscopy may be utilized for treatment of septic arthritis of the pediatric knee, with success reported in ages from 3 months to 12 years. There is limited data on the ability to arthroscopically assess articular structures and ensure adequate evaluation without arthrotomy. Hypothesis/Purpose: The purpose of this study is: (1) utilize arthroscopy in small cadaveric knees to improve qualitative and quantitative knowledge of pediatric articular structures and (2) to obtain pilot data for common procedures performed in pediatric patients Methods: Five small pediatric cadaveric specimens (1-4 years) underwent arthroscopy (2.7 mm Stryker arthroscope). Medial and lateral compartments were assessed for meniscus size/mobility/height, compartmental joint space, ACL insertion, patellar chondral height and length, and position of the medial patellofemoral ligament were recorded. Utilizing standard anterior medial and lateral portals, the ability to visualize the structures of the posteromedial and posterolateral compartments was recorded. Procedures pertinent to immature ACL reconstruction and meniscal repair (unstable discoid) were critically evaluated to provide source data for future work. Results: Prior to arthroscopy, all specimens underwent volume-assessed knee insufflation (average 11.4 cc normal saline). Arthroscopic visualization of the menisco-capsular attachment was possible posteromedially in 4/6, and posterolaterally in 5/6 knees. Qualitative arthroscopic relationships were similar to adult references; including patellar-trochlear articulation and lateral meniscal positional relationship to the ACL insertion (see Figure 1). The ACL center was within 2 mm of the posterior aspect of the anterior horn of the lateral meniscus in all specimens. The average height of the medial compartment space under valgus load was 1.5 mm (1 – 2 mm), and lateral space under varus was 2.2 mm (2-3 mm); further emphasizing the need for small joint instruments. The width of the medial and lateral menisci are noted in Table 1. All-inside meniscal devices designed for skeletally mature specimens should be used with caution (Figure 1). Traditionally described inside-out technique for immature ACL reconstruction with an iliotibial band demonstrated significant proximity of the passing device to the neurovascular bundle (Figure 1). Conclusion: The entirety of the small knee is assessable via standard diagnostic arthroscopy, when a 2.7mm arthroscope is utilized. These findings suggest that intra-articular pathology can be reliably identified utilizing this surgical technique. However, the ability to work on the infant meniscus and cartilage with standard arthroscopic instruments is likely limited given the constraints of joint height. : Table 1. Meniscal width of the medial and lateral meniscus as measure by a microprobe. Figure 1. Arthroscopic and gross images of an infant cadaveric knee 11 year old). (A) ACL insertion into the tibia. Note the relationship of the anterior horn of the lateral meniscus to the ACL Insertion. (B) The patellocrochiear articulation with a well formed troctilea, (C) Medial patellofemoral ligament as it inserts onto the patella. Marking in the ligament 1') indicates centroid of the ligament based on superficial anatomy. (D) Pilot study of placement of an all-inside meniscal repair device (Stryker AIR) The size of implant is 70% of the height of the lateral meniscus, .1E) Image of a dissected popliteal fossa of a small knee. Curved clamp )black arrow) was placed as if to facilitate passage of the !Thin a extra-articular ACL reconstruction with the dicta:fiat hand. Note the proximity to the posterior neurovascular structures (Yellow = artery; blue = nerve).